Radical compassion : learning to love yourself and your world with the practice of RAIN - Brach, Tara (Viking Life, 2019)
Tara Brach is an in-the-trenches teacher whose work counters today's ever-increasing onslaught of news, conflict, demands, and anxieties--stresses that leave us rushing around on auto-pilot and cut off from the presence and creativity that give our lives meaning. In this heartfelt and deeply practical book, she offers an antidote: an easy-to-learn four-step meditation that quickly loosens the grip of difficult emotions and limiting beliefs. Each step in the meditation practice (Recognize, Allow, Investigate, Nurture) is brought to life by memorable stories shared by Tara and her students as they deal with feelings of overwhelm, loss, and self-aversion, with painful relationships, and past trauma--and as they discover step-by-step the sources of love, forgiveness, compassion, and deep wisdom alive within all of us.